Pédaler pour de bonnes causes - Maïa Bouatouch Legrand (Genre, Sexualité et Société)
This article shows that the privilege of challenging gender and class norms attached to cycling as a mode of transportation in the city of Cairo is socially differentiated, and that so is the interest in the normalization of female cycling as a mobility practice. At the intersection between urban and space studies, gender studies and development studies, it aims at contributing to the understanding of mobilities in the Carene megapole, in a context of cycling promotion by international agencies as well as local authorities. It should be read in the continuity of previous works exploring sexual harassment in Egypt as a public issue, through an original case of appropriation of its rhetoric to advocate for the cause of female cycling. At last, this work reflects how the ramadan period offers an opportunity for women to experiment unusual mobilities when attached to a renewed form of performing the expected duty of charity.